PROSPECTS FOR THE DEVELOPMENT OF PILGRIMAGE TOURISM (ON THE EXAMPLE OF KOSON DISTRICT) - Safarov , I.B.; Rasulov, F.I. (Educational Research in Universal Sciences, 2023)
The article explores the features of the development of pilgrimage tourism and the objects of pilgrimage tourism located in Koson district, and provides brief information about shrines, in addition, proposals and recommendations for the development of pilgrimage tourism in Koson district have been developed.